A glimpse into the pipeline of anti-obesity medication development: combining multiple receptor pathways - Park, Christine; Kim, Yushin; Raygani, Sawye; Grunvald, Eduardo (Frontiers in Endocrinology, 2025)
Obesity has been historically a stubborn chronic metabolic disease, resistant to multiple therapeutic modalities. Although effective in the short-term for some people, lifestyle interventions have proven difficult to maintain in the long-term. Metabolic bariatric surgery is the most effective treatment for durable weight loss and improvement of obesity-related conditions but is invasive and vastly underutilized. For decades, patients and clinicians confronted a wide gap between lifestyle modification and bariatric procedures. Anti-obesity pharmacotherapy was plagued by either safety concerns or very modest effectiveness. Recently, the availability of highly effective medications has given patients living with obesity hope for better health. These advances represent a culmination of many years of scientific progress regarding our understanding of human weight regulation and the beginning of a new era in treating metabolic diseases. In fact, many molecules are under investigation for obesity therapy, some with novel mechanisms. Since data on these putative agents are appearing at accelerated speed, the aim of this review is to provide an updated synopsis of emerging agents, highlighting the correlation between efficacy and combination strategies.